Feasibility of a mobile-based system for unsupervised monitoring in Parkinson’s disease - Bouça-Machado, Raquel (2021)
© 2021 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https://creativecommons.org/licenses/by/4.0/).